2019
DOI: 10.20944/preprints201902.0154.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deforestation, Climate Change and Food Security Nexus in Sub-Sahara Africa: Content Analysis

Abstract: Like the rest of the globe, Forests in Sub-Saharan Africa (SSA) continue to play a vital role when it comes to food security from the perspective of forest function of climate regulation, water provision, and soil protection. Nevertheless, most of the recent deforestation practices in various countries indicate that the region could face severe food insecurity in the near future since there are already signs of shortage in food production. This study, therefore, examines deforestation, climate change, and food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…SDG 8 ‘Decent Work and Economic Growth’ is related to the ‘Zero Hunger’ target since countries with high rates of malnutrition and food insecurity may have a high loss of gross domestic product ( 26 ). SDG 13 ‘Climate Action’ is of major importance, especially to some of Africa’s most vulnerable societies, since climate change increases droughts, floods, and other extreme weather events, with detrimental effects on food production ( 27 ). SDG 14 ‘Life Below Water’ and SDG 15 ‘Life on Land’ relate to loss of biodiversity, acidification of the oceans, and soil degradation, which threaten the ability to produce food ( 22 ).…”
Section: Synergies Among the Sdgs To Achieve ‘Zero Hunger’mentioning
confidence: 99%
See 1 more Smart Citation
“…SDG 8 ‘Decent Work and Economic Growth’ is related to the ‘Zero Hunger’ target since countries with high rates of malnutrition and food insecurity may have a high loss of gross domestic product ( 26 ). SDG 13 ‘Climate Action’ is of major importance, especially to some of Africa’s most vulnerable societies, since climate change increases droughts, floods, and other extreme weather events, with detrimental effects on food production ( 27 ). SDG 14 ‘Life Below Water’ and SDG 15 ‘Life on Land’ relate to loss of biodiversity, acidification of the oceans, and soil degradation, which threaten the ability to produce food ( 22 ).…”
Section: Synergies Among the Sdgs To Achieve ‘Zero Hunger’mentioning
confidence: 99%
“…Annually, about 13 million hectares of forests are lost due to deforestation, partly by agriculture, logging, mining, and infrastructure development. Deforestation is a significant factor in promoting climate change through increased emission of greenhouse gases, thus altering temperature and weather patterns globally ( 27 , 39 ).…”
Section: Synergies Among the Sdgs To Achieve ‘Zero Hunger’mentioning
confidence: 99%
“…Studies carried out in sub-Saharan Africa have concluded that the subsistence agriculture is the main driver in the poorest rural populations, often associated with deforestation for charcoal production and/or forest fires [15,16]. Thus, some authors link deforestation to food security, with the most frequent causes being agriculture [17] and exploitation of biomass as fuel [18]. In Angola, the main proximate drivers are the overextraction of timber resources, clearing for agricultural purposes, unregulated burning, and overgrazing [19].…”
Section: Introductionmentioning
confidence: 99%
“…Charcoal production in rural areas causes large environmental impact, especially in comparison with that generated by fuelwood, mainly in periurban areas [7]. This activity, which is continuously growing in Africa, is one of the main causes of deforestation and forest degradation both in Africa and Angola [18,20]. One of the main problems related to charcoal production in the Angolan Miombo is the lack of data about the potential productive capacity of this ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The nexus concept refers to the interconnected and interdependent management between the water, energy, agricultural, and environmental sectors. It is based on the good governance of each of these sectors, and provides for the design and implementation of more efficient and sustainable policies and actions (Hoff, 2011;WEF, 2011;Bamwesigye et al, 2019).…”
Section: Introductionmentioning
confidence: 99%